Characteristic of Cervical Cancer in Reproductive Woman (Under 40 years old) at Prof. I.G.N.G. Ngoerah Denpasar Bali from January - December 2023 - Suwiyoga, Ketut Suwiyoga; Budiana, i Nyoman Gede Budiana; Mahendra, I Nyoman Bayu; Winata, I Gde Sastra Winata; Saspriyana, Kade Yudi Saspriyana; Prayudi, Pande Kadek Aditya Prayudi; Ongko, Eric Gradiyanto Ongko; Hitasari, I Gusti Ayu Made Putri; Septiani, Winty Septiani; Mardana, I Wayan Rivandi Pradiyadnya Mardana; Ronaldo, Fransiscus Ronaldo; Yoga, I Putu Bagus Mulyana Yoga (Indonesian Journal of Perinatology, 2024)
Background: Cervical cancer caused 275,000 deaths globally, with the mortality rate up to 52%. In the past 30 years, the percentage of young women affected by cervical cancer has increased, ranging from 10% to 40%. This study aims to describe the case of cervical cancer in reproductive women in Prof Dr. I.G.N.G Ngoerah General Hospital. Method: This is a cross-sectional retrospective descriptive study involving all cases of cervical cancer diagnosed from January to December 2023 in Prof Dr. I.G.N.G Ngoerah General Hospital. Prof Dr. I.G.N.G Ngoerah General Hospital. We included all cases of cervical cancer proven by histopathology or ultrasound reports. Data were tabulated in the table and analyzed using SPSS version 24.0. Result: We involved 61 patients in this study, with the mean age of participants was 33.91± 4.98. Most patients had two children (45.16%). Patients predominantly came with stage IIB (33.87%). Tumor size was varied, with ≤4 cm being more dominant (67.74%). Chemoradiotherapy was preferred for the management of cervical cancer (37.10%) Conclusion: The characteristics of patients with cervical cancer were varied compared to the literature. Multifactorial risk factors of this disease could explain these. The management should be tailored to the clinical condition of the patient's guidance under the available consensus.